PEMBERDAYAAN TANAMAN OBAT KELUARGA DI KALISEGORO, SEMARANG: EDUKASI DAN INOVASI PRODUK HERBAL UNTUK KESEHATAN MASYARAKAT - Nima, Neli Syahida; Eden, Willy Tirza; Savitri, Annisa Aulia; Rahmaniar, Ranita; Faturachman, Gavriel Fauzan; Utami, Mardhiyah Dwi; Ahmada, Muhammad Diqi; Wulandari, Dyah Pramesthi; Az-Zahra, Mela Denova; Ilhami, Muhamad Aris (Universitas Mataram, 2025)
This community service program focuses on enhancing the use of medicinal plant (TOGA) in Kalisegoro, Gunungpati, Semarang, to help residents recognize and apply medicinal plants as an alternative health solution. The activity involved 28 participants, who received education on various TOGA types, their chemical contents, health benefits, and techniques for processing them into value-added products, such as wedang uwuh gummy candy. The program began with a theoretical session, followed by practical planting of six medicinal plant species, including Moringa leaves, Clitoria flowers, Valerian root, turmeric, Morinda fruit, and nutmeg. Participants also engaged in the production of wedang uwuh gummy candy, utilizing herbal ingredients like ginger, sappan wood, lemongrass, cloves, and cinnamon. Evaluation results indicated a high satisfaction level, with an average score of 4.29 out of 5, particularly on aspects of topic relevance and visual aids support. Most participants felt the materials were suited to their needs and beneficial for everyday life. With high enthusiasm from participants, this program is expected to encourage the community to be more independent in utilizing TOGA as both a health alternative and a local business opportunity centered on herbal products. Keywords: TOGA, medicinal plants, wedang uwuh, herbal education, health products